Symbolic Representations as Teachers Reflect on Inclusive Education in South Africa - Elizabeth Lynne Hooijer; Dr. Martyn Van der Merwe; Dr. Jean Fourie (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
The inclusive education movement generated many changes in the education system worldwide, resulting in teachers needing to change their practice and beliefs and implement inclusive teaching strategies to accommodate a more diverse learner population. Numerous professional development courses were conducted in South Africa, however the expected change in attitude and practice proved difficult to achieve for many. Even after attending such courses, teachers found it challenging to establish inclusive learning environments, believing they did not have the necessary skills and resources to teach learners with divergent learning needs. This study explored the pivotal role of teachers and their personal perspectives of themselves as inclusive practitioners in South Africa after attending a professional development course on inclusive education strategies. A qualitative, interpretative research design was utilised whereby visual symbols alongside written reflections were analysed to identify changes in teachers' knowledge, beliefs and practice. Findings revealed that teachers' knowledge had increased, their attitudes towards learners with diverse needs was more positive, they felt more confident in their own abilities and more equipped for the task. Critical reflection emerged as an essential skill for teachers to be able to question their beliefs and rethink their practice but that this skill needed to be actively taught and encouraged in order to change prevailing perceptions of diversity and improve teaching practice.